2012
DOI: 10.1590/s0103-50532012000400007
|View full text |Cite
|
Sign up to set email alerts
|

Trace metals in the urban aerosols of Rio de Janeiro city

Abstract: De janeiro a abril de 2009, amostras de partículas suspensas (TSP) e de materiais particulados (PM 10 e PM 2.5 ) foram coletadas de uma área urbana característica altamente impactada pelo tráfego de veículos. As concentrações de metais nestas amostras foram determinadas por ICP-OES (espectroscopia de emissão por plasma indutivamente acoplado). Ca, Mg, Fe e Al foram os metais mais abundantes presentes em TSP e PM 10 , com concentrações maiores que 427 ng m -3 . Em PM 2.5 , os metais mais abundantes foram Fe e C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
4
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 26 publications
2
14
4
9
Order By: Relevance
“…Range of the concentration median values of Cu in this study were higher than those reported in Acerra, Italy [11], Tampico, Mexico [23] and Athens, Greece [30], but lower than those reported for Silesia, Poland [27] and Algiers, Algeria [25]. Fe median concentrations in the study site were higher than the reported value for Rio de Janeiro, Brazil [31], Riohacha, Colombia [28], Tampico, Mexico [23] and Acerra, Italy [11], but lower than registered value in Algiers, Algeria [25] and Silesia, Poland [27]. Range of the concentration median values of Mg found in this study was higher than reported values for Rio de Janeiro, Brazil [31], Tijuana, Mexico [29], Colima, Mexico [32] and Riohacha, Colombia [28].…”
Section: Discussioncontrasting
confidence: 81%
“…Range of the concentration median values of Cu in this study were higher than those reported in Acerra, Italy [11], Tampico, Mexico [23] and Athens, Greece [30], but lower than those reported for Silesia, Poland [27] and Algiers, Algeria [25]. Fe median concentrations in the study site were higher than the reported value for Rio de Janeiro, Brazil [31], Riohacha, Colombia [28], Tampico, Mexico [23] and Acerra, Italy [11], but lower than registered value in Algiers, Algeria [25] and Silesia, Poland [27]. Range of the concentration median values of Mg found in this study was higher than reported values for Rio de Janeiro, Brazil [31], Tijuana, Mexico [29], Colima, Mexico [32] and Riohacha, Colombia [28].…”
Section: Discussioncontrasting
confidence: 81%
“…In RJ, some studies have been performed regarding chemical analyses on PM composition (Gioda et al, 2011a; Godoy et al, 2009; Loyola et al, 2012; Mateus et al, 2013; Paulino et al, 2010; Quiterio et al, 2004a). Various epidemiological studies made in RJ link PM exposure to health conditions such as respiratory diseases (Castro et al, 2009) and increased pediatric visits due to bronchial obstruction (Moura et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Others mention that EF < 10 indicates origin by local soil, while values in the range of 10-5000 indicate elements mostly emitted from anthropogenic sources (Smichowski et al, 2005;Loyola et al, 2012;Guéguen et al, 2012;Ferreira et al, 2012). In this work, these two points of view will be observed in the discussion, in association with PCA-MLRA.…”
Section: Enrichment Factormentioning
confidence: 81%